(untitled) (Caleidoscopio. Revista de Italianistica de ADILLI, 2026)
The examination of the links between Futurism and Fascism focuses particularly on Futurism’s discursive configuration, which emerged in the first decade of the 20th century with a manifesto whose aggression did not shy away even from extermination. The patriotic and vitalist components that stand out in Futurism are evaluated both from the perspective of the diverse artistic movements that converged within it and within the framework of an Italian aesthetic system spanning from the beginning of the century to the postwar period. This approach demonstrates a degree of originality on the recovery of forgotten or archived bibliography, such as Guillermo de Torre’s Historia de las literaturas de vanguardia.